THE DEVELOPMENT OF STUDENT WORKSHEETS BASED ON SCIENTIFIC APPROACH WITH PHET SIMULATIONS IN THE SUBJECT MATTER OF VIBRATIONS AND WAVES - Sulastri, Fitri
The COVID-19 pandemic affects the educational aspects of the learning process. Face-to-face learning in schools is changing to online distance learning (PJJ). The platform used for online PJJ is WhatsApp. Practicum is a means of supporting science learning. PJJ only allows practicing virtually with the help of simulations (dry lab). The platform used is PhET. Vibration and wave material is abstract, so a simulation is used to make it easier to understand. Practicum using PhET Simulations is accompanied by student worksheets (LKPD) as practical instructions. LKPD can facilitate students to learn independently in understanding the material through the assignments provided. The aim of this research is to make LKPD based on a scientific approach assisted by PhET Simulations on vibration and wave material. The research method used is development research using the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation. This research resulted in LKPD that have been validated by a physics education lecturer and a science teacher. The results of the LKPD assessment from the presentation aspect obtained a percentage of 90% (very good), the material aspect obtained a percentage of 92% (very good), and the linguistic aspect obtained a percentage of 87% (very good). LKPD is then implemented for class IX students at Junior High School in Tasikmalaya. The vibration worksheet was completed by 18 students and the wave worksheet was completed by 16 students. The average value of vibration LKPD is 80 which means it meets the KKM value (79), while the wave LKPD is 73 which means it does not meet the KKM value. The value of regular learning outcomes (without PhET) from the science teacher in the previous semester for vibration and wave material was 63. The results of LKPD scores based on the scientific approach assisted by PhET are higher than the scores of regular learning outcomes. The results of the student response questionnaire to LKPD have a positive response with a percentage of 27% strongly agree and 68% agree and a negative response with a percentage of 5% disagree. Indicators regarding students who understand better about vibration and wave material when using LKPD assisted by PhET Simulations get a percentage of 86% agree.